SWAMPLAND CONFLICT DYNAMICS IN SOUTH KALIMANTAN: ANALYSING THE ROOT CAUSES OF CONFLICT - Akmal, Helmi; Arisanty, Deasy; Angriani, Parida; Handy, Muhammad Rezky Noor (International Conference On Social Science Education, 2024)
Wetland conflicts are particularly pronounced in regions rich in natural resources, such as the peat swamp areas in South Kalimantan. Local communities in these areas rely on the land for small-scale agriculture. In contrast, conservation efforts to prevent forest and land fires have led to clashes between community needs and government conservation policies, escalating the conflict. This paper employs a literature review to overview the conflicts occurring in peat swamp areas comprehensively. The analysis includes research articles published in national and international journals over the past two decades, from 2010 to 2024. Findings indicate that overlapping land ownership, policies with limited community participation, and the impacts of climate change are the primary drivers of conflict escalation. The consequences of these conflicts span social, economic, cultural, and environmental dimensions, including reduced livelihood access, ecosystem degradation, and loss of local cultural values. This study underscores the need for a more inclusive and participatory approach to land management that involves local communities, supporting both ecosystem sustainability and social stability in the region.